A new exploration of health risk assessment quantification from sources of soil heavy metals under different land use. (December 2018) - Huang, Jinhui; Guo, Shiting; Zeng, Guang-ming; Li, Fei; Gu, Yanling; Shi, Yahui; Shi, Lixiu; Liu, Wenchu; Peng, Shuying
Abstract: Heavy metals in the topsoil affected adversely human health through inhalation, ingestion and dermal contact. The health risk assessment, which are quantified from soil heavy metals sources under different land use, can provide an important reference basis for preventing and controlling the soil heavy metals pollution from the source. In this study, simple statistical analysis and Positive Matrix Factorization (PMF) were used to quantify sources of soil heavy metals; then a health risk assessment (HRA) model combined with PMF was proposed to assess quantificationally the human health risk (including non-cancer risk and cancer risk) from sources under residential-land, forest-land and farm land. Xiang River New District (XRNQ) was chosen as the example and four significant sources were quantitatively analyzed in the study. For cancer risk, industrial discharge was the largest source and accounted for about 69.6%, 69.7%, 56.5% for adults under residential-land, forest-land and farm-land, respectively. For non-cancer risk, industrial discharge was still the largest significant source under residential-land and forest-land and accounted for about 41.7%, 39.2% for adult, respectively; while agricultural activities accounted for about 51.8% for adult under farm-land. The risk trend of children, including cancer risk and non-cancer risk, was similar with adults. However, the non-cancer risk areas of adults affected by industrial discharge was higher than that of children, while the cancer risk areas of adults were on the contrary. The new exploration was useful to assess health risk quantification from sources under different land use, thus providing certain reference in preventing and controlling the pollution from the source for local authorities effectively. Graphical abstract: Image 1 Highlights: Four sources of soil heavy metals in XRND were identified by Positive Matrix Factorization model. The joint health risk of soil heavy metals quantified from sources under different land uses was obtained for a first effort. Industrial discharge was the largest source of human cancer risk.